Remote sensing based water balance to estimate evapotranspiration and irrigation water requirements. Case study: grape vineyards - Campos I.; Boteta L.; Balbontín C.; Fabião M.; Maia J.; Calera A. (The use of remote sensing and geographic information systems for irrigation management in Southwest Europe, 2012)
In this paper the basis for the incorporation of remote sensing data into a soil water balance through the relationship between the basal crop coefficient (Kcb) and vegetation indices (VI) for grape vineyards is described. The remote sensing soil water balance has been applied in previous studies obtaining accurate estimates of actual evapotranspiration and crop coefficient in grape vineyard, and this methodology is evaluated in order to estimate irrigation necessities in an irrigated vineyard in Albacete, Spain. The model was also applied in vineyards under high deficit irrigation management. The model results: total irrigation necessities, crop evapotranspiration, and water stress coefficient (Ks) are analyzed. The evolution of Ks was compared with experimental measurements of stem water potential ((s). Ks calculated present values between 0.2 and 0.4 during July and August, indicating severe stress levels. The s tendency coincides with the modelled Ks, showing a parallel evolution and values of about -1.4 MPa during the stress period. The evidences presented indicate that Kcb derived from VI overestimate the actual crop coefficient under water stress conditions. In these cases, it is therefore essential to properly estimate the stress coefficient in order to accurately estimate actual crop evapotranspiration and crop coefficient.